Factors influencing dental appearance satisfaction in adolescents: a cross-sectional study conducted in Southern Brazil - Gregori Franco Boeira; Mabel Miluska Suca Salas; Diogo Conceição Araújo; Alexandre Severo Masotti; Marcos Britto Correa; Flávio Fernando Demarco (Universidade Estadual de Campinas, 2016)
The perception of dental aesthetic appearance may affect social interaction and psychological status, influencing dental needs and the search for treatments. Aim: To investigate the satisfaction with dental appearance and influencing factors among adolescents. Methods: The study was carried out among adolescents aged 14 to 19 years attending a private high school in Brazil. Data on demographic information, the perception of dental appearance, previous aesthetic treatments and wish to perform dental treatments were collected in the school. Data were analyzed using Pearson's chi-square test or Linear Trend. Multivariate analysis was performed using the Poisson regression. Results: A total of 531 adolescents (Response rate = 98.3%) answered the questionnaire. The prevalence of dissatisfaction with dental appearance was 17.4%. Almost 65% had history of previous orthodontic treatment and 16% performed dental bleaching. Approximately 45% of children wished to undergo orthodontics and 54.8% to bleach their teeth. Dissatisfaction with dental appearance was associated with individuals unsatisfied with dental color (95% IC[1.73;4.32]), those perceiving poor dental alignment (PR3.16 95% IC[2.11;4.72]) and those wishing orthodontic treatment (PR2.9; 95% IC[1.79; 4.70]). Conclusions: The prevalence of dissatisfaction was considerable and was associated with aesthetic concerns such as tooth color, dental alignment and with the wish for orthodontics. In this young population, a large part of adolescents had already performed orthodontic and bleaching treatments and wished to perform those treatments again. Satisfaction with dental appearance could affect the adolescents' behavior regarding search for dental treatment, thus causing possible overtreatment.